Book Reviews (Heythrop journal, 2000)
Books reviewed Gail Corrington Streete, The Strange Woman: Power and Sex in the Bible Athalya Brenner (ed), Judges (A Feminist Companion to the Bible. Second Series 4) Athalya Brenner (ed), Ruth and Esther (The Feminist Companion to the Bible. Second Series 3) Wendy Cotter, Miracles in Greco-Roman Antiquity: A Sourcebook for the Study of New Testament Miracle Stories N. T. Wright and Marcus J. Borg, The Meaning of Jesus Daniel J. Harrington, Invitation to the Apocrypha François Bovon, Ann Graham Brock and Christopher R. Matthews (eds), The Apocryphal Acts of the Apostles (Harvard Divinity School Studies) A. J. M. Wedderburn, Beyond Resurrection Richard Fardon, Mary Douglas: An Intellectual Biography Catherine Pickstock, After Writing: On the Liturgical Consummation of Philosophy Lucy Gardener, David Moss, Ben Quash and Graham Ward, Balthasar at the End of Modernity John R. Quinn, The Reform of the Papacy André Corten, Pentecostalism in Brazil: Emotion of the Poor and Theological Romanticism John R. Tyson (ed), Invitation to Christian Spirituality: An Ecumenical Anthology Adrian Thatcher (ed), Spirituality and the Curriculum James Howard-Johnston and Paul Antony Hayward (eds), The Cult of the Saints in Late Antiquity and the Early Middle Ages: Essays on the Contribution of Peter Brown Georgia Frank, The Memory of the Eyes: Pilgrims to Living Saints in Late Antiquity (The Transformation of the Classical Heritage 30) R. M. Grant, Early Christians and Animals Anthony Meredith, Gregory of Nyssa (The Early Church Fathers) Anna Silvas, Jutta and Hildegard: The Biographical Sources Christoph. T. Maier, Crusade Propaganda and Ideology: Model Sermons for the Preaching of the Cross Diana Norman, Siena and the Virgin: Art and Politics in a Late Medieval City State David Dymond (ed), The Register of Thetford Priory, Part 1, 1482–1517 David Dymond (ed), The Register of Thetford Priory, Part 2, 1518–1540 Wilfrid McGreal, John of the Cross (Fount Christian Thinkers) Peta Dunstan, This Poor Sort: A History of the European Province of the Society of St Francis Yirmiyahu Yovel, Dark Riddle: Hegel, Nietzsche and the Jews Terence Irwin (ed), Classical Philosophy Christopher Bruell, On the Socratic Education: An Introduction to the Shorter Platonic Dialogues Gareth B. Matthews, Socratic Perplexity Ralph McInerny, Aquinas and Analogy Paul Vincent Spade (ed), The Cambridge Companion to Ockham René Descartes, Regulae ad Directionem Ingenii: Rules for the Direction of the Natural Intelligence (Studies in the History of Ideas in the Low Countries) Robert Sokolowski, Introduction to Phenomenology Janna Thompson, Discourse and Knowledge: Defence of a Collectivist Ethics David Carr and Jan Steutel (eds), Virtue Ethics and Moral Education Daniel McInerny, The Common Things: Essays on Thomism and Education Gary Gutting, Pragmatic Liberalism and the Critique of Modernity (Modern European Philosophy) David Schmidtz and Robert E. Goodin, Social Welfare and Individual Responsibility: For and Against Peter H. Sedgwick, The Market Economy and Christian Ethics